Evaluation of Cardioprotective Effect of 3,5,3′-Tri-iodo-L-thyronine in Isoproterenol-Induced Cardiotoxicity - Vinay Mishra; Priya Ghumatkar; Maulik V. Patel; Shilpesh Devada; Ramchandra Ranvir; Prabodha Swain; Rajesh Sundar; Rajesh Bahekar; Mukul R. Jain (International Journal of Endocrinology)
T3 (3,5,3′-triiodothyronine) has drawn relatively little attention in relation to cardiovascular (CVS) diseases. The present study was designed to evaluate the cardioprotective action of T3 in isoproterenol-(ISO-) induced cardiac toxicity. Female Wistar rats were exposed with ISO (100 mg/kg, body weight, subcutaneously) for 2 days at the interval of 24 h followed by T3 (3 μg/kg, body weight, orally) treatment for 3 days. Positive control rats received only ISO (100 mg/kg, body weight, subcutaneously) for 2 days at the interval of 24 hrs. Control group animals received normal saline as a vehicle. As expected, ISO-induced significant changes were observed in low-density lipoprotein, total cholesterol, ALT, CK-MB to TCK ratio, and prolongation of QT interval in electrocardiogram, which is toward normalization after T3 treatment. Lower heart weight, upregulation of cardiac myosin heavy chain alpha (MHC-α), and reduced inflammatory cell infiltration, myonecrosis, vacuolar changes, and a trend toward normal cardiac muscle fiber architecture in microscopic examination of cardiac tissue further support the cardioprotective effect of T3.